Lexical and grammatical meaning’s ambiguity in the job creation law number 6 of 2023 - Purwono, Prahoro Yudo; Datang, Frans Asisi (Universitas Muhammadiyah Malang, 2024)
Job Creation Law Number 6 of 2023 was designed to revise and replace Job Creation Law Number 4 of 2022, which had previously replaced Job Creation Law Number 11 of 2020. Despite the primary objective of this law to address deficiencies in the previous laws, significant potential linguistic issues still exist, namely lexical and grammatical ambiguities. This is evident in several articles whose meanings remain ambiguous, dual, and contradictory with other articles or laws, opening opportunities for diverse interpretations and creating legal uncertainty. This study aims to delineate the forms of lexical and grammatical ambiguity in the Job Creation Law Number 6 of 2023. The research method applied is qualitative research method, focusing on analyzing micro discourse structure, encompassing lexical and grammatical meanings. The research findings reveal that several words and phrases are prone to misinterpretation. Lexical ambiguity is found in the words 'dapat' (can/may), 'memperhatikan' (considering), and phrases such as 'tidak mampu' (unable), 'istirahat panjang' (long rest), 'Paling Banyak' (most), and 'Paling Lama' (longest). In contrast, grammatical ambiguity is observed in phrases like 'Serta harus' (and must) and 'Diberitahu' (informed). These ambiguities are present in Article 17 Paragraph 1, Article 81 Paragraph 33, Article 81 Paragraph 25, Article 42 Paragraph 3, Article 17 Paragraph 32, and the explanatory section of Article 8 Part 33. Based on the research findings, it is crucial to propose a review or re-evaluation of articles that have the potential for controversy due to lexical or grammatical ambiguity.